Determinação do teor de extrato etéreo de grãos de oleaginosas através de diferentes processamentos - Haydt Castello Branco Van Cleef, Eric [UNESP]; De Oliveira, Daiana [UNESP]; Aparecida Bonato, Melina [UNESP]; Maria Bertocco Ezequiel, Jane [UNESP]; De Souza Gonçalves, Josemir [UNESP] (My University, 2012)
The objective of this work was to determine the ether extract content of peanut and canola seeds, with extraction in Soxhlet apparatus and with three types of processing: grinding in ball mill type; maceration in mortar and grind into micro mill after maceration in mortar. Data were analyzed in an entirely randomized design with 3 treatments and 12 replicates, submitted to variance analysis and the means were compared using Tukey test (P<0.05) with routines of the SAS statistical package. The largest percentage of ether extract was obtained in the treatment which the peanuts were subjected to a greater number of extractions (56.43%), and all treatments presented different results(P <0.05). In canola grains, it was observed that the extraction with the method of grinding in ball mill and the method of sequential extraction (macerate + ground in micro mill) were statistically similar (43.52 and 42.35% respectively), and these methods were more efficient (P <0.05) to extract the ether extract than the treatment in which the grains were only macerated. For peanut grains it was concluded that the most efficient method was the sequential one and to the canola grain, it can be used only a grinding mill as samples processing witch will be submitted to ether extract extraction.
Determination of oil seed grains ether extract content through different processing
Keywords: Canola; Feedstuff analysis; Peanut; Arachis hypogaea; Brassica napus; Brassica napus var. napus